(untitled) (International Journal of Engineering and Computer Science, 2018)
Authentication represents the process which verifies the identity of a user who has got the rights to make certain actions or changes in an application or on a device. Methods for authenticating users into their devices and online services have to be user-friendly and must uphold privacy. This paper aims on discussing the different methods adopted for authentication using biometrics rather than using the conventional methods for authentication such as PIN or Password. Biometrics can be used as a very effective method against cyber theft. They are so unique that it is nearly impossible to precisely reproduce a user characteristic.